2021
DOI: 10.1007/s00402-021-03894-0
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical versus non-anatomical configuration of double coraco-clavicular tunnel technique in acromioclavicular joint reconstruction

Abstract: Purpose Horizontal instability is a common problem after acromioclavicular joint injuries. The aim of this study was to evaluate if there is a difference regarding horizontal stability between an anatomical and a non-anatomical configuration of the double tunnel coraco-clavicular ligament reconstruction of the acromioclavicular joint. Methods Thirteen acromioclavicular joints of human cadaveric shoulders in ethanol-glycerin fixation were included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The largest cluster consists of nine authors, but their research is focused on between 2016 and 2018. The Schoebel T[ 21 ]-centered cluster (7 authors), whose research in this field is concentrated after 2020, is a relatively new and closely cooperative research team, and it is also a team with great potential in the current field. The top three authors of total link strength are Scheibel [ 17 ](TLS = 15), Boyer [ 22 ](TLS = 15), and Barth [ 23 ] (TLS = 14), which shows that the three authors have done more cooperation with others.…”
Section: Resultsmentioning
confidence: 99%
“…The largest cluster consists of nine authors, but their research is focused on between 2016 and 2018. The Schoebel T[ 21 ]-centered cluster (7 authors), whose research in this field is concentrated after 2020, is a relatively new and closely cooperative research team, and it is also a team with great potential in the current field. The top three authors of total link strength are Scheibel [ 17 ](TLS = 15), Boyer [ 22 ](TLS = 15), and Barth [ 23 ] (TLS = 14), which shows that the three authors have done more cooperation with others.…”
Section: Resultsmentioning
confidence: 99%
“…Usually failed conservative therapy over a time period of months is the indication for AC-joint resection or resection of the lateral clavicle [ 14 ]. This procedure can be performed either in an open fashion or arthroscopically [ 21 , 28 , 31 ]. Because of the preservation of the superior capsule, the preference and better outcome are attributed to the arthroscopic technique nowadays [ 4 , 7 , 15 , 23 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that fixation with suture or suture tape for AC ligament repair have demonstrated similar biomechanical strength to the native AC and coracoclavicular (CC) ligaments. 8 Arthroscopic techniques are less invasive compared to open procedures. 4,9 Pan and colleagues 10 conducted a metaanalysis comparing the arthroscopic tape reconstruction to the hook and plate technique for Rockwood types III-V AC dislocations and found similar outcomes between the techniques for postoperative reduction (coracoclavicular distance weighted mean difference [WMD] 0.24, 95% confidence interval [CI] À0.67, 1.15; P ¼ .602 and function of the AC joint (constant score WMD 6.12; 95% CI À3.84, 16.08; P ¼ .229); however, tape fixation resulted in less postoperative pain and improved cosmesis compared to the hook and plate technique (VAS WMD À0.69; 95% CI À1.10, À0.27; P ¼ .001).…”
mentioning
confidence: 99%